2022
DOI: 10.1210/endocr/bqac067
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Cellular and Systemic Metabolism: Metabolic Syndrome in Systemic Lupus Erythematosus

Abstract: A high prevalence of metabolic syndrome (MetS) has been reported in multiple cohorts of systemic lupus erythematosus (SLE) patients, most likely as one of the consequences of autoimmune pathogenesis. Although MetS has been associated with inflammation, its consequences on the lupus immune system and on disease manifestations are largely unknown. The metabolism of immune cells is altered and overactivated in mouse models as well as in patients with SLE, and several metabolic inhibitors have shown therapeutic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
1
3
1
Order By: Relevance
“…29,30 Some medications used to treat SLE or T2DM also exhibit therapeutic effects on each other. 31,32 However, our study did not demonstrate a causal link between SLE and T2DM, unlike previous observational studies. This disparity might arise from our focus on the East Asian population and the absence of investigations among other populations.…”
Section: Establish An Increased Risk Of Sle Development Among Eastcontrasting
confidence: 99%
“…29,30 Some medications used to treat SLE or T2DM also exhibit therapeutic effects on each other. 31,32 However, our study did not demonstrate a causal link between SLE and T2DM, unlike previous observational studies. This disparity might arise from our focus on the East Asian population and the absence of investigations among other populations.…”
Section: Establish An Increased Risk Of Sle Development Among Eastcontrasting
confidence: 99%
“…This result suggested that cholesterol biosynthesis activated IL6-STAT3 signaling. Consistent with a recent report that serum starvation conditions enhanced cholesterol biosyn-thesis [41], we expounded on the function of starvation in the manipulation of IL6 signaling by ADAM9. Rapidly proliferating cancer cells require sufficient cholesterol metabolites to support and maintain growth, survival, energy consumption, and signal transduction [42].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, standard immunosuppressive treatments are linked to significant toxicities, including myelosuppression and infections (44). The use of glucocorticoids has greatly improved survival in patients with LN; however, long-term use is associated with safety concerns, including infections, elevated risk of cardiovascular disease, metabolic side effects (45), and accrual of damage from SLE, which are major causes of morbidity and mortality in SLE (5,(46)(47)(48)(49). Hence, treatment strategies that aim to minimize glucocorticoid exposure while maintaining treatment efficacy have substantial clinical value (45).…”
Section: Unmet Needs In Current Management Of Lnmentioning
confidence: 99%